Protocol for lateral patterning of van der Waals heterostructures using sequential chemical vapor deposition - Soonyoung Cha; Hyeuk-Jin Han; Ji-Hoon Ahn; Gangtae Jin (STAR Protocols)
Summary: Previous work demonstrates that scalable area-selective deposition of van der Waals monolayers enables tunable design of atomically thin electronic and photonic platforms. Here, we present a protocol for lateral patterning of MoS2–WS2 heterostructures using sequential chemical vapor deposition. We describe steps for constructing patterned lateral heterostructures with alternating channels from nanometers to micrometers. This protocol has potential application in next-generation atomically thin electronic circuits.For complete details on the use and execution of this protocol, please refer to Lee et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.